TJNPR 2023
DOI: 10.26538/tjnpr/v7i8.3
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants of Moulay Yaâcoub Province in Morocco: An Ethnobotanical and Biodiversity Survey

Abstract: Currently, many medicinal plants continue to be utilized for the treatment and prevention of diseases. Numerous studies conducted in Morocco indicate that aromatic and medicinal plants (MAPs) have been used for centuries to cure various ailments. The distribution of therapeutic herbs through herbal markets plays a crucial role in preserving cultural heritage. this study was conducted among residents of the Moulay Yaâcoub province with the aim of documenting ethnobotanical knowledge and identifying different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…These results are consistent with similar ethnobotanical studies, conducted in the north of Morocco and other regions, of the practice of using medicinal plants according to age groups. [14][15][16][17][18] Usage of cannabis sativa according to gender The questionnaire was mainly completed by male respondents (92.9%), who reported using Cannabis for therapeutic reasons, such as relaxation, anxiety reduction, and enhanced pleasure. They also considered Cannabis as a safer substitute for other harmful drugs that they had previously used for similar purposes.…”
Section: Data Description Sociodemographic Data Of the Study Populati...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with similar ethnobotanical studies, conducted in the north of Morocco and other regions, of the practice of using medicinal plants according to age groups. [14][15][16][17][18] Usage of cannabis sativa according to gender The questionnaire was mainly completed by male respondents (92.9%), who reported using Cannabis for therapeutic reasons, such as relaxation, anxiety reduction, and enhanced pleasure. They also considered Cannabis as a safer substitute for other harmful drugs that they had previously used for similar purposes.…”
Section: Data Description Sociodemographic Data Of the Study Populati...mentioning
confidence: 99%
“…This is consistent with the existing ethnobotanical studies in Morocco on medicinal plants, which indicated that the ancestral sources are the key channels for information transmission. 14,[83][84][85][86] Factors associated with the plant's uses The aim of conducting this study was to explore the factors influencing the utilization of Cannabis sativa among participants through rigorous statistical analysis. Employing the chi-square test, we investigated the correlation between various forms of cannabis use and participants' characteristics.…”
Section: Other Uses Of Cannabis Sativamentioning
confidence: 99%